Bibliografia di storia della psichiatria italiana 1991-2010 - Fiorani, Matteo (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2010)
This bibliography renders account of the over two thousand books on the history of Italian psychiatry that have appeared over the last twenty years. The aim is thus to support the demand for a new historiographic approach to psychiatry which has come regularly to the fore since the 1990s. It is also intended to respond to the need for comparison with the consistently topical reflections handed down to us from the past on issues such as madness, mental health, psychiatry and society. Bibliographic database: www.fupress.net/storiapsichiatria